NITRATE, PHOSPHATE AND SILICATE CONCENTRATION WITH THE ABUNDANCE OF DIATOMS ON SUIR ESTUARY MERANTI ISLAND - Siregar, Meiyanto; Nurrachmi, Irvina; Yoswaty, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted in December 2016 in the Suir Estuary Meranti Island. The purpose of this study was to analyze the correlations between the concentration of nitrate, phosphate and silicate as well as an abundance of diatoms, to provide information about fertility waters seen from the content of nitrate, phosphate and silicate as well as an abundance of diatoms in the water. The research was used purposive sampling method with 3 region and each region to be 10 station point. The results showed that the concentration of Nitrate, Phosphate and Silicate i.e; 0,122 mg/L ; 0,021 mg/L ;0,059 mg/L. Diatom species were found 10 species i.e; Isthmia, Ceralaulina dentata, Rhizosolenia indica, Skeletonema costatum, Bidulphia pulchella, Rhizosolenia alata, Aulacoseria granulate, Nitzschia serianata, Lepctocylindrus anmeus and Ceratium furca. An abundance of diatoms at region 1 , region 2 and region 3 as much as 86.1111Ind/L; 111.1111Ind/L; 112.50000 Ind/L. The results of Regression test showed that nitrate concentrations correlations with diatom abundance of very strong correlation with the value of r (correlation coefficient) = 0,606. Relations with the abundance of diatoms phosphate concentrations are very weak correlations with the value of r (correlation coefficient) = 0.239. Relations with the silicate concentration of diatom abundance of weak correlationss with the value of r (correlation coefficient) = 0,556 .Key Words : Nitrate, Phospate, Silicate, Abundance Diatoms.